The Influence of Culture and Mentality on Retirement Planning in Kazakhstan - Bakhtgalieva, Aigerim; Tasheva, Madina; Yin-Fah, Benjamin Chan (Asian Business Review, 2018)
The world is experiencing ageing phenomenal and the topic of individual retirement planning is becoming more important than before. Many studies focus on factors toward retirement planning, but limited researches studied how the culture and mentality influence the retirement planning in Kazakhstan country. This qualitative study has interviewed ten interviewees to explore how the culture and mentality concern contribute to their retirement planning decision. This paper entails the opinions and experiences about retirement planning among the younger generations in Kazakhstan.